Methuosis key gene ARF6 as a diagnostic, prognostic and immunotherapeutic marker for prostate cancer: based on a comprehensive pan-cancer multi-omics analysis - Yongjin Yang; Liangliang Qing; Chengyu You; Qingchao Li; Wenbo Xu; Zhilong Dong (Discover Oncology)
Abstract Background Prostate cancer (PCa) is a leading cause of cancer-related mortality among men worldwide. Despite progress in the understanding of tumor biology, the prognosis for advanced prostate cancer remains poor, necessitating the identification of novel diagnostic, prognostic, and therapeutic biomarkers. Methuosis, a recently identified form of programmed cell death (PCD), is characterized by cytoplasmic vacuole accumulation and subsequent cell rupture, distinct from classical apoptosis and necrosis. The key regulatory gene in Methuosis, ARF6 (ADP-ribosylation factor 6), has emerged as a potential marker for cancer diagnosis and treatment. However, its role in prostate cancer and other malignancies remains insufficiently understood. Methods In this study, we performed a comprehensive pan-cancer multi-omics analysis to investigate the role of ARF6 in Methuosis across multiple cancer types, with a specific focus on PCa as the primary context. Using data from public databases, including RNA sequencing, gene expression profiling, and clinical outcomes, we assessed the association between ARF6 expression and patient prognosis in PCa within this broader pan-cancer framework. Additionally, we employed functional enrichment analyses and survival analysis to explore the potential of ARF6 as a diagnostic and prognostic marker for prostate cancer. Immunotherapy-related gene expression signatures were also evaluated to determine the therapeutic relevance of ARF6. Results ARF6 was significantly overexpressed in PCa tissues compared to normal tissues and was associated with poor prognosis (p < 0.05), particularly in advanced and metastatic stages. Receiver operating characteristic (ROC) analysis revealed a diagnostic AUC of 0.792 for ARF6. Functional analyses indicated that ARF6 regulates pathways critical to cell migration, invasion, and drug resistance. Moreover, ARF6 expression showed a strong negative correlation with immune checkpoint markers, such as PD-L1 (r = − 0.74), suggesting its potential as an immunotherapy target. These findings underscore ARF6’s pivotal role in Methuosis and its promise as a biomarker in PCa. Conclusion ARF6 is a key regulator of Methuosis in prostate cancer, contributing to tumor progression, metastasis, and resistance to treatment. Our findings support the potential of ARF6 as a diagnostic, prognostic, and immunotherapeutic target in prostate cancer. Further experimental validation is needed to confirm these observations and to explore the therapeutic implications of targeting ARF6 in cancer treatment.